Analisis Kebermaknaan Hidup (Meaning of Life) Perempuan Badut Jalanan di Kota Padang - Wikeoktafianti, Wikeoktafianti; Afdhal, Afdhal (TSAQOFAH, 2026)
The phenomenon of women working as street clowns in Padang City indicates that informal work in public spaces is not only related to meeting economic needs, but is also associated with psychological dimensions, particularly meaning in life. This study aims to describe meaning in life, the process of searching for meaning in life, and the daily activities that support the construction of meaning in life among female street clowns in Padang City. This study employed a qualitative approach with a descriptive design, involving two female street clowns selected through snowball sampling. Data were collected through in-depth interviews, observation, and documentation, and were then analyzed through the stages of data reduction, data display, and conclusion drawing. Data validity was maintained through triangulation. The results showed that female street clowns were able to find meaning in life through responsibility toward their families, experiences of love and affection, and an attitude of acceptance toward the life conditions they faced. This meaning in life was reflected in the freedom to choose their attitude, the desire to endure and work independently, and the ability to interpret suffering as part of the life process. These findings affirm that meaning in life is not determined by the type of work or social status, but by the way individuals interpret their life experiences. This study contributes to the development of guidance and counseling scholarship, particularly in understanding the dynamics of meaning in life among socially vulnerable groups.